A monocenter study on 6-year changes in parathyroid hormone, blood calcium and phosphorus qualification rates in maintenance hemodialysis patients - FU Bin; GUO Zong-lin; GAO Xiang; REN Ting-ting; YANG Mei; PENG Qiao-li (Linchuang shenzangbing zazhi)
Objective To know about the 6-year changes in parathyroid hormone(PTH), and blood calcium and phosphorus qualification rates in maintenance hemodialysis patients(MHD) in a single center. Methods Respectively, 244, 313, 325, 434, 418 and 331 patients with MHD lasting for more than 6 months were selected in Department of Nephropathy of the Eleventh People’s Hospital of Chengdu from 2012 to 2017. Among all the patients, some ones received medication for treatment of SHPT in 2012, and the ones who had no response to medication after 2013 underwent parathyroidectomy. The data on their age, sex, primary diseases and dialysis course were collected, and their indices including blood iPTH, calcium, phosphorus and albumin were determined. P<0.05 was considered to be statistically significant. Results(1).The course of hemodialysis was prolonged from 3.9±3.3 years to 6.1±4.0 years(P=0.000), and the proportion of males increased(x~2=4.542,P=0.033), but there was no difference in age(P=0.653) and primary disease(both x~2=0.000, P=1.000).(2). PTH qualification rates were 50.82%, 54.95%,54.77%,56.22%,54.07% and 56.19 %, respectively. And blood calcium qualification rates were 39.75%,38.02%,37.85%,44.24%,41.63% and 43.50% respectively. And blood phosphorus qualification rates were 39.34%, 39.62%, 45.85%, 40.32%, 34.69% and 31.72% respectively. There was no difference in qualification rates of PTH(x~2=1.632, P=0.201), blood calcium(x~2=0.811, P=0.368) and blood phosphorus(x~2=3.589, P=0.058) through 6 years.(3). The curve of prevalence rates of SHPT through the 6 years was U-shaped. The prevalence rates were 27.87%, 21.41%, 22.15%, 24.65%, 28.71% and 29.00% respectively, with higher rates in 2017 and 2012. but no difference(x~2=0.089, P=0.766), and with lower rated in 2013 and 2014. The prevalence rates of hypoparathyroidism were 21.31%, 23.64%, 23.08%, 19.12%, 17.22% and 14.80%%,respectively, with the rate in 2017 notably lower than that in 2012(x~2=4.108,P=0.043).(4). The prevalence rates of hypercalcemia were 24.58%, 33.55%, 24.62%, 31.34%,26.79% and 13.29% respectively, with the rate in 2017 notably lower than that inn 2012(x~2=12.099, P=0.021). The prevalence rates of hypocalcemia were 35.66%, 28.43%, 37.54%, 24.42%, 31.58% and 43.20% respectively, with no differences(x~2=3.333, P=0.068) through the 6 years.(5). The prevalence rates of hyperphosphatemia were 51.23%, 51.23%, 52.72%, 44.31%, 51.38% and 57.66%, respectively, with the rate in 2017 notably higher than that in 2012(x~2=7.361, P=0.007). The prevalence rates of hypophosphatemia were 9.43%, 7.67%, 9.85%, 8.29 %, 7.66% and 5.74% respectively, with no differences(x~2=2.819, P=0.093) through the 6 years.(6). In the patients with parathyroidectomy, qualification rates of PTH, blood calcium and phosphorus were 17.02%, 36.17% and 44.68%, respectively; the prevalence rates of hypoparathyroidism, hypocalcemia and hypophosphatemia were 46.81%, 53.19% and 10.64% respectively. The prevalence rate of SHPT, hypercalcemia and hyperphosphatemia were 36.17%, 10.64% and 44.68% respectively. Conclusions(1). The qualification rates of PTH, blood calcium and phosphorus tend to be stable during the 6 years.(2). The prevalence rates of hypoparathyroidism and hypercalcemia both decline, but hyperphosphatemia increases.(3).Parathyroidectomy can improve the qualification rate of PTH in the patients with SHPT who have no response to medication, reduce the incidence of hypercalcemia, and increase the risk of low PTH at the same time.